Where Is The “Nursing” In The RNFA/PNS Role? - Groetzsch, Grace (Operating Room Nurses Association of Canada Journal, 1997)
Many individuals who are not perioperative nurses struggle with the notion that the Registered Nurse First Assistant (RNFA) or Perioperative Nurse - Sur- gery (PNS) role is “nursing.” The Canadian Nurses Association (1993) aptly states that an expert nurse’s advanced practice may look very much like some of the activities of physicians, but that does not mean it is not nursing practice (p.20).